2020
DOI: 10.1002/cpe.5985
|View full text |Cite
|
Sign up to set email alerts
|

A decision system for computational authors profiling: From machine learning to deep learning

Abstract: In this study, we tackle the problem of author profiling. The aim of the proposed approach is to determine the author's age and gender. Once the user connects to the company website, this company collects the available data about him (which is usually very limited). Then, the user receives a service recommendation according to his gender and age. Thus, a context-specific decision-making system based on these limited data is required to produce an efficient classification. Such a decision system allows companie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…From their findings in their work, they identified that the proposed work results are outperformed than most of the well-known methods to AP. Piot-Perez-Abadin developed [18] a method for detecting the profile like gender. They considered both semantic and psycholinguistic features in their experiment.…”
Section: Existing Approachesmentioning
confidence: 99%
“…From their findings in their work, they identified that the proposed work results are outperformed than most of the well-known methods to AP. Piot-Perez-Abadin developed [18] a method for detecting the profile like gender. They considered both semantic and psycholinguistic features in their experiment.…”
Section: Existing Approachesmentioning
confidence: 99%